The effectiveness of the use of visual materials in a grade V social studies unit - Khan, Ata-ullah 1917- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1966)
The purpose of this study is to find out whether pupils who were taught social studies using visual materials will retain significantly greater means in achievement and retention than those taught without visual materials.
Thesis (Master of Education)--University of the Philippines Diliman; 1966
Keywords: Visual aids; Teaching -- Aids and devices